A scoping review of the literature of research ethics committees and ethics review framework in Pakistan: what we know and what we still need to learn - Farah Asif; Sultan, Faisal; Masood, Iqra; Baig, Shahtaj; Ekmecki, Perihan Elif; Vaswani, Vina; Bhutta, Zulfiqar; Crawley, Francis (Journal of the Pakistan Medical Association, 2023)
Objective: To map literature on research ethics committees, institutional review boards and ethics review framework in Pakistan to identify key insights during public health emergencies and normal times. Method: The systematic scoping review was conducted in April 22, and comprised literature search on PubMed, World Health Organisation Global Index Medicus and Summons databases for articles published between January 2005 and February 2022. Information extracted included authors’ names, year of publication, title, study methodology, and key insights under the heads of challenges and solutions. Due to data heterogeneity, key themes were identified and analysed. Results: Of the 2,190 studies initially identified, 21(0.95%) were subjected to full-text review, and, from among them, 9(45%) were analysed in detail. There were 4 key insights identified: research ethics committees and institutional review boards in Pakistan remain unregulated as they are currently not registered or accredited by a competent national-level authority; most members of such committees are not formally trained to implement the mandate; internal and external pressures hinder independent decision-making of such committees; and other issues hindering the functionality and performance of research ethics committees and institutional review boards. Conclusion: Despite existing publications calling for urgent policy and regulatory reforms, there is a dearth of literature and minimal policy actions underline the fact that ethics review remains a neglected area in Pakistan. Key Words: Ethics, Pakistan, Bioethics, Ethics committees, Institutional review board.